Genu Recurvatum after Tibial Tuberosity Fracture - Senthil T. Nathan; Shital N. Parikh (Case Reports in Orthopedics)
Fractures of the tibial tuberosity are infrequent injuries that occur during adolescence. Displaced tibial tuberosity fractures are typically treated with open reduction and internal fixation. Since these fractures occur at or near skeletal maturity, growth disturbances are not seen. This paper presents a case, the first report to our knowledge, of genu recurvatum deformity after open reduction and internal fixation of a tibial tuberosity fracture. A successful treatment plan of tibial tuberosity osteotomy with proximal tibial opening wedge osteotomy was used for the correction of genu recurvatum deformity and to maintain appropriate patellar height. At eighteen-month followup, the deformity remains corrected with satisfactory functional results. This case highlights the importance of recognition of potential complications of fracture management in adolescence.